2021
DOI: 10.3389/fimmu.2021.727850
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Response Following Vaccination With the BNT162b2 mRNA COVID-19 Vaccine in Patients Affected by Primary Immunodeficiencies

Abstract: Mass SARS-Cov-2 vaccination campaign represents the only strategy to defeat the global pandemic we are facing. Immunocompromised patients represent a vulnerable population at high risk of developing severe COVID-19 and thus should be prioritized in the vaccination programs and in the study of the vaccine efficacy. Nevertheless, most data on efficacy and safety of the available vaccines derive from trials conducted on healthy individuals; hence, studies on immunogenicity of SARS-CoV2 vaccines in such population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 49 publications
13
100
0
Order By: Relevance
“…No patients contracted a SARS-CoV-2 infection up to six months of observation after vaccination. Our results show the vaccine to be highly effective in this population, as measured by antibody levels, with only one individual with DS not seroconverting after the first dose, and compared to other vulnerable populations [11][12][13][14], which showed a suboptimal response to the routine vaccination schedule.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…No patients contracted a SARS-CoV-2 infection up to six months of observation after vaccination. Our results show the vaccine to be highly effective in this population, as measured by antibody levels, with only one individual with DS not seroconverting after the first dose, and compared to other vulnerable populations [11][12][13][14], which showed a suboptimal response to the routine vaccination schedule.…”
Section: Discussionmentioning
confidence: 68%
“…For the general population, the administration of a two-dose SARS-CoV-2 messenger ribonucleic acid (mRNA) vaccination was found to be safe and effective in immunocompetent individuals [9,10] and was approved for administration in December 2020. However, our group and others have shown that other cohorts of immune-compromised adolescents and young adults, such as solid organ transplanted patients [11,12] and those with primary immune deficiencies [13,14], have a suboptimal immunization with the routine vaccination schedule. In line with this, there is an urgent need to establish an effective immunization schedule against COVID-19 in individuals with DS previously known to have had a B cell dysfunction [5].…”
Section: Ofmentioning
confidence: 83%
“…The most important outcome of COVID-19 vaccination is a balanced, co-ordinated cellular immune response to the virus ( 25 , 30 ). This implies at least some T cell function is required for vaccine efficacy ( 50 ). Given what was noted in the NZHS and NZCS, COVID-19 vaccines will provide at least partial protection in most immunocompromised patients.…”
Section: Approach To Immunocompromised Patientsmentioning
confidence: 99%
“…It remains to be determined if heterologous primary immunisation, with mRNA and adenovirus-based vaccines generates a robust cellular response, as seen with humoral responses in healthy individuals ( 58 ). Again, monitoring T cell responses following vaccination will provide reassurance ( 50 , 55 ).…”
Section: Approach To Immunocompromised Patientsmentioning
confidence: 99%
See 1 more Smart Citation